EFFECT of late plnting oN emergence, Tillering and YIELD Of VARIOUS VARIETIES OF WHEAT - M. Akhtar; N. Ahmad; M. Nasrullah; B. Ali; A. R. Zahid; M. I. Shahid (Journal of Animal and Plant Sciences, 2012)
A field experiment was conducted to evaluate the effect of late planting on yield of different varieties of wheat, in agro ecological conditions of Bahawalpur zone. The study included four sowing times starting from 1st December to 16th January during the year 2007-08 with an equal interval of fifteen days. Four wheat varieties viz. Inqlab-91, Punjab-96, MH-97 and Bhakkar-2002 were included in the experiment. The experiment was laid out in randomized complete block design with Split Plot arrangement having four replications, keeping sowing dates in main plots and wheat varieties in sub plots. The plot size was 2.4m x 8 m. The data were analyzed statistically using computer statistical program MSTATC. Analysis of variance was applied to test the overall significance of the data. Tukey’s honestly least difference test at 5% probability level was used to compare the differences among treatment means. Sowing dates and varieties both significantly affected the germination, tillering and grain yield. Among time of sowing, 1st December sowing gave significantly maximum mean grain yield of 4412 kg ha-1 against the minimum mean grain yield of 2197 kg ha-1 for 16th January sowing. Among wheat varieties Bhakkar-2002 gave significantly maximum mean grain yield of 3445 kg ha-1, whereas MH-97 was the lowest yielder 3185 kg ha-1. Emergence impaired due to delayed sowing owing to low temperature for germination, resulting in poor stand establishment and reduced the number of productive tillers and ultimately the final grain yield.
Keywords: Time of sowing; wheat varieties; germination; tillering and grain yield.